Intermittency of gravity wave potential energies and absolute momentum fluxes derived from infrared limb sounding satellite observations - Ern, Manfred; Preusse, Peter; Riese, Martin (Atmospheric Chemistry and Physics, 2022)
Atmospheric gravity waves contribute significantly to the driving of the global atmospheric circulation. Because of their small spatial scales, their effect on the circulation is usually parameterized in general circulation models. These parameterizations, however, are strongly simplified. One important but often neglected characteristic of the gravity wave distribution is the fact that gravity wave sources and, thus, the global distribution of gravity waves are both very intermittent. Therefore, time series of global observations of gravity waves are needed to study the distribution, seasonal variation, and strength of this effect. For gravity wave absolute momentum fluxes and potential energies observed by the High-Resolution Dynamics Limb Sounder (HIRDLS) and Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) limb sounding satellite instruments, we investigate the global distribution of gravity wave intermittency by deriving probability density functions (PDFs) in different regions as well as global distributions of Gini coefficients. In the stratosphere, we find that intermittency is strongest in mountain wave regions, followed by the polar night jets and by regions of deep convection in the summertime subtropics. Intermittency is weakest in the tropics. A better comparability of intermittency in different years and regions is achieved by normalizing observations by their spatially and temporally varying monthly median distributions. Our results are qualitatively in agreement with previous findings from satellite observations and quantitatively in good agreement with previous findings from superpressure balloons and high-resolution models. Generally, momentum fluxes exhibit stronger intermittency than potential energies, and lognormal distributions are often a reasonable approximation of the PDFs. In the tropics, we find that, for monthly averages, intermittency increases with altitude, which might be a consequence of variations in the atmospheric background and, thus, varying gravity ...